High Counts and Anthracene Degradation Ability of Streptococcus mutans and Veillonella parvula Isolated From the Oral Cavity of Cigarette Smokers and Non-smokers - Moussa, Hams A.; Wasfi, Reham; Abdeltawab, Nourtan F.; Megahed, Salwa A. (Frontiers in Microbiology, 2021)
The composition and metabolic functions of oral microbiota are affected by many factors including smoking leading to several health problems. Cigarette smoking is associated with changes in oral microbiota composition and function. However, it is not known if the depletion of certain bacterial genera and species is due to specific toxins in cigarette smoke, or indirectly due to competition for colonization with smoking-enriched bacteria. Therefore, the aim of this study was to determine the effect of cigarette smoking on the microbial prevalence and polycyclic aromatic hydrocarbons (PAHs) biodegradation of selected enriched and depleted oral bacteria from oral microbiota compared to that in non-smokers. Samples of oral rinse from smokers and non-smokers were collected (n = 23, 12 smokers and 11 non-smokers) and screened for oral bacterial strains of Streptococcus mutans, Lactobacillus spp., and Veillonella spp. Comparing counts, S. mutans, V. tobetsuensis and V. dispar showed higher counts in smokers compared to non-smokers while the Lactobacillus spp. were higher in non-smokers. Lactobacillus fermentum was prevalent in smokers, representing 91.67% of the total isolates. The biodegradation potential of anthracene; a representative of PAHs of collected isolates, in single and mixed cultures, was assayed with anthracene as the sole source of carbon using 2,6-dichlorophenol indophenol (2,6-DCPIP) as indicator. S. mutans isolates recovered from smokers showed higher degradation of anthracene compared to those recovered from non-smokers. The anaerobic anthracene biodegradation activity of V. parvula isolates from non-smokers was the highest among all isolates of the three recovered genera from the same subject. The anthracene biodegradation potential of Lactobacillus spp. was variable. Combinations of isolated bacteria in co-cultures mixtures showed that Lactobacillus spp. interfered with anthracene biodegradation ability along with the viable counts of S. mutans and V eillonella spp. In conclusion, oral dysbiosis due to cigarette smoking was observed not only due to changes in oral bacterial relative abundance but also extended to bacterial functions such as anthracene biodegradation tested in this study. Microbe–microbe interactions changed the anthracene biodegradation potential and growth of the microbial mixture compared to their corresponding single isolates, and these changes differ according to the constituting bacteria.